Platinum and Gold Species on Non-Reducible Oxides as Active and Stable Catalysts for the Low-Temperature Water-Gas Shift Reaction. - Wang, Yuan. (2017)
Abstract: Hydrogen is of interest because it is a clean, safe and efficient energy source. For the low-temperature fuel cell application, the water-gas shift (WGS) reaction is an important step in upgrading hydrogen streams produced from fuel reforming operations. It has been challenging to develop low-temperature WGS catalysts that are both highly active and stable at the operation conditions of proton exchange membrane (PEM) fuel cell systems. The current catalysts used in industrial WGS reactors, Cu/ZnO/Al2O3, are unsuitable for fuel cell systems because they are pyrophoric, lack thermal stability, and require activation procedures. Noble metal (Au, Pt, Pd etc.) on oxide support (CeO2, TiO2, FeOx etc.) catalysts have emerged as attractive catalyst alternatives possessing high activity and stability for the low-temperature WGS reaction. These have to be designed with trace amounts of valuable metals to be economical. In this thesis, platinum and gold species on non-reducible silica and alumina supports were investigated as novel catalysts for the low-temperature WGS reaction. In particular, encapsulated platinum in the form of core-shell Pt@SiO2 material was prepared by a reverse microemulsion technique, while supported gold was prepared by deposition on modified γ-alumina supports with OH-rich surfaces through various hydrothermal treatments. Addition of alkali ions, associating Pt and Au species with the OH-rich oxide support surfaces, rendered the corresponding Pt-Na@SiO2 and Na-Au/Al2O3-OH samples active and stable catalysts for the low-temperature WGS reaction, whereas their alkali-free counterparts showed low activity and poor stability. Samples were characterized by BET surface area, UV-Visible Spectroscopy (UV-Vis), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), high resolution transmission electron microscopy (HRTEM) and CO chemisorption. Temperature-programmed reduction (TPR) measurements and cyclic TPR tests were conducted using the reactant CO as the reductant. Catalytic activities of the samples were evaluated for the WGS reaction under various gas conditions in temperature-programmed surface reaction (TPSR) and steady-state modes, and compared with other Pt- and Au-based catalysts prepared on various oxides supports by different methods. The Pt-Ox(OH)-M or Au-Ox(OH)-M species, where M denotes an alkali ion, are concluded to be very promising for further development of low-temperature WGS reaction catalysts. The apparent activation energy, Eapp, for the reaction is the same for these new catalysts and for other Pt- or Au-based catalysts previously reported. For the Pt-based catalysts, Eapp = 70 ± 5 kJ/mol, and for Au-based catalysts, Eapp = 45 ± 5 kJ/mol. This is true whether a reducible or a non-reducible support is used, the latter stabilized only with the help of alkali promoters. Hence, the active site comprises oxygen and hydroxyl groups, but is independent of the type of the support used.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Maria Flytzani-Stephanopoulos.; Committee: Hyunmin Yi, and Terry Haas.; Keyword: Chemical engineering.